2018
DOI: 10.1016/j.jgr.2017.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Molecular signaling of ginsenosides Rb1, Rg1, and Rg3 and their mode of actions

Abstract: Ginseng has gained its popularity as an adaptogen since ancient days because of its triterpenoid saponins, known as ginsenosides. These triterpenoid saponins are unique and classified as protopanaxatriol and protopanaxadiol saponins based on their glycosylation patterns. They play many protective roles in humans and are under intense research as various groups continue to study their efficacy at the molecular level in various disorders. Ginsenosides Rb1 and Rg1 are the most abundant ginsenosides present in gin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
156
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(161 citation statements)
references
References 100 publications
4
156
0
1
Order By: Relevance
“…20(S)-Rg3 is a compound that has many biological effects of preventing ischemia-reperfusion injury, reducing oxygen free radicals, antioxidation, and inhibiting the activity of voltage-regulated pathways. Studies have reported that 20(S)-Rg3 as a nontraditional therapy has protective effects on diabetes itself, as well as diabetic cardiomyopathy, diabetic retinopathy, and atherosclerosis in DM [23,24]. Kang et al [20] reported 20(S)-Rg3 prevents the progression of renal damage and dysfunction in type 2 diabetic rats via inhibiting oxidative stress and advanced glycation end-product formation.…”
Section: Discussionmentioning
confidence: 99%
“…20(S)-Rg3 is a compound that has many biological effects of preventing ischemia-reperfusion injury, reducing oxygen free radicals, antioxidation, and inhibiting the activity of voltage-regulated pathways. Studies have reported that 20(S)-Rg3 as a nontraditional therapy has protective effects on diabetes itself, as well as diabetic cardiomyopathy, diabetic retinopathy, and atherosclerosis in DM [23,24]. Kang et al [20] reported 20(S)-Rg3 prevents the progression of renal damage and dysfunction in type 2 diabetic rats via inhibiting oxidative stress and advanced glycation end-product formation.…”
Section: Discussionmentioning
confidence: 99%
“…Another molecule, ginseng, also known as red ginseng (Panax ginseng, Araliaceae), is a well-known medicinal plant and popular source of saponins. Several studies identified the biological active components of ginseng, the ginsenosides, that were shown to play many protective roles [416]. The most frequently used and studied ginsenosides, Rg1, Rg3, and Rb1, were investigated for their effect on α-syn aggregation in vitro [417,418].…”
Section: Other Antioxidant Strategiesmentioning
confidence: 99%
“…Much of the pharmacological research has shown that Panax ginseng has potent immune modulation, vasorelaxation, anti-oxidation, antiinflammation, and anticancer properties (14). Panax ginseng contains many active components such as ginsenosides, peptides, essential oil and polysaccharides, among which, ginsenosides (e.g., Rg3 and Rb1) are considered an excellent option for their anticancer property (15). Ginseng and its active components have been reported as an adjuvant treatment to synergistically enhance efficacy of conventional therapy (e.g., chemoand radio-therapeutics), reduce the risk of development and recurrence of some types of cancer (e.g., stomach, liver, pancreas, and colon cancer), and improve host intrinsic response to cancer and quality of patients' life (16).…”
Section: Some Single Chinese Herbal Medicines With Properties Of Spirmentioning
confidence: 99%